2014
DOI: 10.1186/1471-2458-14-1131
|View full text |Cite
|
Sign up to set email alerts
|

Public knowledge of cardiovascular disease and its risk factors in Kuwait: a cross-sectional survey

Abstract: BackgroundCardiovascular disease (CVD) is estimated to cause 46% of all mortalities in Kuwait. To design effective primary and secondary prevention programs, an assessment of a population’s prior CVD knowledge is of paramount importance. There is scarcity of data on the existing CVD knowledge among the general Kuwaiti population. Hence, this study was performed to assess the level of knowledge towards CVD types, warning symptoms of heart attack or stroke, and CVD risk factors. It also explored public views on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

48
141
17
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(209 citation statements)
references
References 27 publications
48
141
17
3
Order By: Relevance
“…Our analysis of patients' knowledge of the coronary artery disease, myocardial infarction, and prevention, like numerous other reports [6, 9-11, 15, 16], did not reveal significant differences in this regard between men and women, although some researchers claim such a difference does exist [17]. This, however, does not signify that the knowledge of women and men are at equal levels.…”
Section: Discussionsupporting
confidence: 62%
“…Our analysis of patients' knowledge of the coronary artery disease, myocardial infarction, and prevention, like numerous other reports [6, 9-11, 15, 16], did not reveal significant differences in this regard between men and women, although some researchers claim such a difference does exist [17]. This, however, does not signify that the knowledge of women and men are at equal levels.…”
Section: Discussionsupporting
confidence: 62%
“…7,25 A study conducted in Kuwait to assess public knowledge of cardiovascular disease (CVD) risk factors reported similar findings, while another conducted in Jordan reported higher levels of knowledge among their cohort. 15,16 Smoking, high blood pressure and high cholesterol have been rated as factors posing the greatest risk for CHD. 8 Pereira et al reported that the prevalence, awareness, treatment and control of these risk factors in developing countries are coming closer to those in developed countries.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] Recent studies in this region have focused on screening for obesity, dietary patterns and diabetes mellitus. [18][19][20] There is therefore an urgent need to understand baseline knowledge levels of CHD among the Omani population before designing appropriate and effective interventions to promote awareness.…”
mentioning
confidence: 99%
“…Cardiovascular disease (CVD) is one of the most preventable causes of death in the world, due to the fact that the majority of its risk factors are preventable or controllable, such as hypertension, dyslipidemia, diabetes, obesity, smoking, lack of physical activity, stress, unhealthy dietary practices and diabetes [4,5] .…”
Section: Introductionmentioning
confidence: 99%
“…Patient education is key in order to detecting changes in body weight or clinical status early enough to allow the patient or a healthcare provider an opportunity to institute treatments that can prevent clinical deterioration in those patients [5,6] . The main goal of cardiac rehabilitation is to prompt patients participate in their therapeutic treatment regimen to such an extent that they can achieve living almost a normal life.…”
Section: Introductionmentioning
confidence: 99%